Satire and Absurdity in Edward Albee’s the American Dream - Ardiya Ardiya; Prih Febtiningsih (Faculty of Teacher Training and Education, 2019)
This research is intended to elaborate and analyze satire and absurdity in Edward Albee’s The American Dream. This research is also intended to relate the satires and absurdity to the reality of life in America in the late of 1950’s. This research is conducted through a method of library research by analyzing the play and relating to other supporting references. This research is conducted in the frame of literary studies by applying the mimetic approach. The result of the research shows that the play contains satires and absurdity. The satires are directed to American progress, artificial value, alienation, and women’s domination. The absurdity in the play is found in the conventions of pure theater, clowning, fooling, and mad-scene, verbal nonsense, and allegorical element. Both satire and absurdity in the play portray the reality of life in America during the Cold War period.